Sedia Aku Sebelum Hujan: Analisis Tindak Tutur dan Implikatur Lirik Lagu karya Idgitaf - Himmah Amaliyaturrahmah (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study aims to examine pragmatic aspects, particularly speech acts and implicatures, in the lyrics of the song “Sedia Aku Sebelum Hujan” by Idgitaf. By applying a qualitative descriptive method through pragmatic content analysis techniques, this study examines locutionary, illocutionary, and perlocutionary speech acts based on Austin's theory, as well as conversational implicatures based on Grice's framework. The results show that the song lyrics are dominated by expressive and commissive illocutionary acts that serve to express sacrifice, vulnerability, and unconditional commitment. Locutionary acts play a role in constructing a literal narrative about protection and relationship inequality, while perlocutionary acts are aimed at evoking feelings of security and gratitude in the listener. Furthermore, the study of implicature reveals deeper implied meanings related to self-sacrifice, acceptance of inequality in relationships, and anticipatory commitment, which are often conveyed through the metaphors of “rain” and “war”. This study concludes that the power of lyrics lies not only in explicit romantic expressions, but also in the strategic use of language to perform actions and convey implicit values of devotion, reflecting the complex dynamics of human relationships, even when they are unbalanced. These findings emphasize the importance of pragmatic analysis in fully understanding the communicative and artistic impact of song lyrics.